The influence of alcohol on genioglossus single motor units in men and women during wakefulness. Issue 3 (19th December 2022) - Avraam, Joanne; Dawson, Andrew; Nicholas, Christian L.; Fridgant, Monika D.; Fan, Feiven Lee; Kay, Amanda; Koay, Zi Yi; Greig, Rachel; O'Donoghue, Fergal J.; Trinder, John; Jordan, Amy S.
Abstract : New Findings: What is the central question of this study? How does alcohol intake, which worsens obstructive sleep apnoea, alter motor control of the genioglossus muscle, an upper airway dilator, in healthy awake human volunteers, and does alcohol alter genioglossus muscle afterdischarge? What is the main finding and its importance? Alcohol consumption had a very minor effect on the activity of the genioglossus in healthy young individuals studied during wakefulness and did not alter afterdischarge, leaving open the possibility that alcohol worsens obstructive sleep apnoea via other mechanisms. Abstract: Alcohol worsens obstructive sleep apnoea (OSA). This effect is thought to be due to alcohol's depressant effect on upper airway dilator muscles such as the genioglossus, but how alcohol reduces genioglossal activity is unknown. The aim of this study was to investigate the effect of alcohol consumption on genioglossus muscle single motor units (MUs). Sixteen healthy individuals were studied on two occasions (alcohol: breath alcohol concentration ∼0.07% and placebo). They were instrumented with a nasal mask, four intramuscular genioglossal EMG electrodes, and an ear oximeter. They were exposed to 8–12 hypoxia trials (45–60 s of 10% O2 followed by one breath of 100% O2 ) while awake. MUs were sorted according to their firing patterns and quantified during baseline, hypoxia and recovery. For the alcohol and placebo conditions, global muscle activity (mean ± SD peak inspiratory EMG = 119.3 ± 44.1 and 126.5 ± 51.9 μV, respectively, P  = 0.53) and total number of MUs recorded at baseline (68 and 67, respectively) were similar. Likewise, the peak discharge frequency did not differ between conditions (21.2 ± 4.28 vs. 22.4 ± 4.08 Hz, P  = 0.09). There was no difference between conditions in the number (101 vs. 88, respectively) and distribution of MU classes during hypoxia, and afterdischarge duration was also similar. In this study, alcohol had a very minor effect on genioglossal activity and afterdischarge in these otherwise healthy young individuals studied while awake. If similar effects are observed during sleep, it would suggest that the worsening of OSA following alcohol may be related to increased upper airway resistance/nasal congestion or arousal threshold changes.